Impact of strategic human resource management practices on perceived organizational performance - Ang, Joo Bee (2008)
This study examined the mediating role of growth satisfaction, satisfaction with job security and pay satisfaction on the relationship between seven strategic human resource management practices (internal career opportunities, extensive formal training, employee participation, clearly defined jobs, employment security, results-oriented appraisals and profit sharing) and perceived organizational performance.